Development of herbal tea using Daun Rerama (Christia Vespertillonis), Kaduk (Piper Sarmentosum) and Stevia (Stevia Rebaudiana)/ Ahmad Hafizi Ahmar, Norazmir Md Nor and Farrah Shafeera Ibrahim - Ahmar, Ahmad Hafizi; Md Nor, Norazmir; Ibrahim, Farrah Shafeera (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The herbal tea was developed using Daun Rerama (Christia Vespertillonis), Kaduk (Piper Sarmentosum) and Stevia (Stevia Rebaudiana) as the main ingredients. Sensory evaluation was conducted and mean score for colour, aroma, taste, aftertaste and overall acceptability for herbal tea was 3.76 ± 0.926, 3.56 ± 1.261, 3.32 ± 1.651, 3.52 ± 1.503 and 3.76 ± 1.091 respectively while for commercialized tea was 6.20 ± 0.866, 5.40 ± 1.000, 3.08 ± 1.801, 3.20 ± 1.683 and 3.84 ± 1.091 respectively. Moreover, results from ANOVA showed that there was significant difference (P < 0.05) between the two samples only in colour and aroma. Besides, sensory shelf life test was conducted and mean score for colour, aroma, taste, aftertaste and overall acceptability for herbal tea that had been stored for three months was 3.88 ± 1.054, 3.48 ± 1.194, 3.44 ± 1.635, 3.48 ± 1.418 and 3.76 ±1.589 respectively while for freshly made herbal tea was 3.76 ± 0.926, 3.56 ± 1.261, 3.32 ± 1.651, 3.52 ± 1.503 and 3.76 ± 1.091 respectively. Moreover, results from ANOVA showed that there was no significant difference (P > 0.05) between the two samples in all of the sensory attributes. In conclusion, the acceptance of the herbal tea quite low compared to commercialized tea. Despite of low mean score on each sensory attributes, the acceptance of the herbal tea after three months period of storage was the same as the herbal tea that was freshly made.